Transformasi Penciptaan Seni Lukis Bali - Suyasa, I Nyoman (Institut Seni Indoensia Surakarta, 2010)
Painting as one means of creating works of art activity experienced a fairly rapid developments changes.This transformation can not be denied again because of the demans of users and the development of technological developments, as well as occuring in the world of art in Bali. Transformation of visual styles in painting in Bali is what will be discussed in this article, of Balinese traditional painting (painting Kamasan), semi traditional painting or so called modern painting (a focus on Pita Maha art and young artists), until in modern painting. Keyword : transformation, painting,Bali